f(0, 1,

g(

g(

R

↳Dependency Pair Analysis

F(0, 1,X) -> F(g(X,X),X,X)

F(0, 1,X) -> G(X,X)

Furthermore,

R

↳DPs

→DP Problem 1

↳Non Termination

**F(0, 1, X) -> F(g(X, X), X, X)**

f(0, 1,X) -> f(g(X,X),X,X)

g(X,Y) ->X

g(X,Y) ->Y

Found an infinite P-chain over R:

P =

F(0, 1,X) -> F(g(X,X),X,X)

R =

f(0, 1,X) -> f(g(X,X),X,X)

g(X,Y) ->X

g(X,Y) ->Y

s = F(g(g(1, 0), g(1, 0)), g(1, 0), g(1, 0))

evaluates to t =F(g(g(1, 0), g(1, 0)), g(1, 0), g(1, 0))

Thus, s starts an infinite chain.

Duration:

0:00 minutes